Galectin-3 as a modifier of anti-microbial immunity: Unraveling the unknowns - Sehrawat, S.; Kaur, M. (NLM (Medline), 2020)
Galectins play diverse roles in pathophysiology of infectious diseases and cancers. Galectin-3 is one of the most studied family member and the only chimeric type lectin. Many aspects of its biogenesis, range of activities, and the disease-modifying potential particularly during microbial infections are yet to be known. We review our current understanding of these issues and also highlight gaps in better defining the immune modulatory potential of galectin-3 during different stages of host responsiveness when an infection sets in. Additionally, we discuss commonly used strategies to disrupt galectin-3 functions both extracellulalry and intracellularly. Existing and improved novel strategies could help fine-tune immune responses to achieve better prognosis of infectious diseases.
Keywords: Anti-microbial immunity; Galectin-3; Intrabodies; Pathophysiology